Development of attitude control system on RCM3400 microcontroller - Yaakop, M.; Sazali, Yaacob, Prof. Dr.; Abdul Rahman, Mohd Saad, Prof Madya; Zain, M.; Paulraj, Murugesa Pandiyan, Prof. Dr.; Hariharan, M.; Nagarajan, R., Prof. Dr.; Kay, W. S.; Arshad, A. S. (Institute of Electrical and Electronic Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/